Anticorrosive water borne paints free from zinc and with reduced phosphate content - Roselli, Sol Natacha (2017)
The objective of this research was to formulate water-borne epoxy coatings free from zinc and with reduced phosphate levels, replacing zinc phosphate by calcium acid phosphate. Lanthanum molybdate was incorporated as a green anticorrosive pigment to enhance paint anticorrosive performance. Paints were assessed by accelerated (salt spray and humidity chambers) and electrochemical tests (ionic resistance and electrochemical noise). Results suggested that zinc phosphate could be replaced by calcium acid phosphate and the phosphate content in the paint ﬁlm reduced to one third. Lanthanum molybdate can act synergistically with phosphates.